Lehet-e vasárnap vadászni? Szabályok vasárnapra - Teofil KOVÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
Is Hunting allowed on Sundays? Rules for the Seventh Day. The present study is part of a longer research project which aims at presenting the international movement for the sanctification of Sunday between 1875 and 1878 in the light of the periodical Evangyéliomi Protestáns Lap (EPL), founded and edited between 1875 and 1878 by Ferenc Balogh (1836–1913), a Reformed church and dogmatic historian and professor of church history in Debrecen, supplemented by domestic news from the periodicals Protestáns Egyházi és Iskolai Lap (PEIL) and Erdélyi Protestáns Közlöny (EPL). Church associations, tenders, religious and secular newsletters, publications and conferences played a major role in the international struggle for a Sunday off. This is how the International Sunday Movement came into being. The professor from Debrecen also supported it and kept the issue of Sunday celebration on the agenda with his Evangyéliomi Protestáns Lap. The issue was not only examined from an ecclesiastical point of view at the time, but its social and health implications were also pointed out. The issue of Sunday rest was of great interest. The problem is not a recent one, but the transformation of economic life has brought the issue to the fore more strongly. Most of the problematic Sunday working has come from the railways, industry, and commerce, with little mention of agriculture.